MODIFIKASI ALAT PENCACAH PLASTIK DENGAN SISTEM PENGGERAK MANUAL - Keristian Panji Karolus; Rudy Poeng; Charles Ch Punuhsingon (JURNAL POROS TEKNIK MESIN UNSRAT, 2018)
The purpose of this study is to modify the plastic chopper and make a plastic counter with a manual drive system.The method used is four steps. The first step is to determine the modification plan. The second step is the selection of the use of modified materials. The third step is to make technical drawings. The fourth step is to make a modified plastic counter.The results of this modification can be obtained by a simple plastic counter unit using a manual drive system with a estimation time of 1012,500 minutes or 16,875 hours. The modified plastic chopper was able to count 69 plastic bottles of mineral water in 1 hour.Â Keywords: Modification, Plastic Counter, Manual Drive System